Design of a serious game for participatory planning of nature-based solutions: The experience of the Edible City Game - Josep Pueyo-Ros; Joaquim Comas; Ina Säumel; Joana A.C. Castellar; Lucía Alexandra Popartan; Vicenç Acuña; Lluís Corominas (Nature-Based Solutions, 2023)
Serious games have been proposed by several studies as a tool to foster civic participatory processes. However, such an endeavour is often prone to failure due to lack of funding or lack of skills on designing serious games. In response to this problem, this paper provides a novel framework for the design of serious games for participatory planning of nature-based solutions, which provides guidance for the definition, content, and evaluation steps. The usefulness of the framework is illustrated with the design of the Edible City Game (ECG), a digital serious game for participatory planning of edible city solutions (urban nature-based solutions with a food component). The designed ECG was then implemented in Tygron, a platform which provides a graphical interface for serious games for urban planning. However, although Tygron provides a user-friendly software to design serious games, our thesis is that the final product still needs a proper design-orientated process to fulfil its purpose. We believe that this framework, as well as our experience using the Tygron platform, can be of great utility to both researchers and practitioners that have considered using serious games in their projects but discarded the idea because of the foreseen resource intensity of the endeavour.